SPHK1 enhances olaparib resistance in ovarian cancer through the NFκB/NRF2/ferroptosis pathway - Kai Teng; Hanlin Ma; Panpan Gai; Xuelian Zhao; Gonghua Qi (Cell Death Discovery)
Abstract PARPis resistance is a challenge in the treatment of ovarian cancer. To investigate the potential mechanism involved in olaparib resistance of ovarian cancer, high-throughput sequencing was performed on olaparib-resistant SKOV3 cell line named SK/Ola. SPHK1 was upregulated in SK/Ola cells and was related to the PFS and OS in ovarian cancer patients. However, the effect and mechanism of SPHK1 on olaparib sensitivity in ovarian cancer were obscure. In this study, we found that SPHK1 promoted olaparib resistance. While, SPHK1 knockdown and SPHK1 inhibitor (PF-543 hydrochloride, named PF-543 in this article) enhanced the effect of olaparib on ovarian cancer cells. In mechanism, SPHK1 activated the NF-κB pathway through promoting p-IκBα degradation. Moreover, SPHK1 inhibited, but PF-543 activated ferroptosis in OC cells. Further investigation revealed that SPHK1 activated NF-κB p65, which in turn transcriptionally regulated NRF2 to inhibit ferroptosis in OC cells. Functionally, NF-κB p65 attenuated the PF-543-induced ferroptosis, and this effect was rescued by ferroptosis inducer erastin and RSL3. We conclude that SPHK1 inhibition triggers ferroptosis by restricting NF-κB-activated NRF2 transcription, thereby enhancing olaparib sensitivity in ovarian cancer. In vivo experiments also confirmed that the SPHK1 inhibitor increased olaparib sensitivity. A combination of SPHK1 inhibitors and olaparib may provide a therapeutic strategy for ovarian cancer.